Vegetation characteristics of forest stands used by woodland caribou and those disturbed by fire or logging in Manitoba - Juha M. Metsaranta; Frank F. Mallory; Dale W. Cross (Rangifer, 2003)
This study examined woodland caribou (Rangifer tarandus caribou) in an area known as the Kississing-Naosap caribou range in west central Manitoba. The vegetation characteristics of areas used by caribou and areas disturbed by fire or logging were measured in order to develop a model to estimate habitat quality from parameters collected during stan¬dard resource inventories. There was evidence that habitat index values calculated using a visual score-sheet index could be used as the basis to relate parameters commonly collected during resource inventories to habitat suitability. Use of this model to select long and short-term leave areas during forest management planning could potentially mitigate some of the negative impacts of forest harvesting. Abundance of arboreal lichen and wind-fallen trees were important predictor variables in the suitability model, but their inclusion did not explain more variance in habitat suitability than models that did not include them. Extreme post-fire deadfall abundance may play a role in predator-prey dynamics by creating habitat that is equally unsuitable for all ungulates, and thus keeping both moose and caribou densities low.